2023
DOI: 10.3390/pharmaceutics15020532
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-DNA Nanoparticles as Drug-Delivery Vehicles for the Treatment of Retinal Diseases

Abstract: Retinal eye diseases are the leading cause of blindness in the Western world. Up to date, the only efficient treatment for many retinal diseases consists of invasive intravitreal injections of highly concentrated drugs. Despite the fact that these injections are unpleasant for the patients, they potentially cause serious side effects, e.g., infections, bleeding within the eye or retinal detachment, especially when performed on a monthly basis, thus decreasing the injection frequency and lowering the desired dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The experiment confirmed improved residence time in porcine and human corneal tissue compared to the original drug, highlighting the potential to increase the in vivo efficiency of these drug delivery systems. Subsequent studies conducted by other research groups have supported the potential of DNA nanocarriers for intraocular drug delivery [ 232 , 233 , 235 ]. In an in vivo experiment reported by one research group, nanoparticles were injected into the eye tissue of rats and it was found that although the drug appeared diffused when compared to injections into the vitreous cavity, adhesion to retinal tissue was still achieved up to 5 days [ 232 ].…”
Section: Exploring Dna Nanostructures As Innovative Vehicles For Opht...mentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment confirmed improved residence time in porcine and human corneal tissue compared to the original drug, highlighting the potential to increase the in vivo efficiency of these drug delivery systems. Subsequent studies conducted by other research groups have supported the potential of DNA nanocarriers for intraocular drug delivery [ 232 , 233 , 235 ]. In an in vivo experiment reported by one research group, nanoparticles were injected into the eye tissue of rats and it was found that although the drug appeared diffused when compared to injections into the vitreous cavity, adhesion to retinal tissue was still achieved up to 5 days [ 232 ].…”
Section: Exploring Dna Nanostructures As Innovative Vehicles For Opht...mentioning
confidence: 99%
“…Subsequent studies conducted by other research groups have supported the potential of DNA nanocarriers for intraocular drug delivery [ 232 , 233 , 235 ]. In an in vivo experiment reported by one research group, nanoparticles were injected into the eye tissue of rats and it was found that although the drug appeared diffused when compared to injections into the vitreous cavity, adhesion to retinal tissue was still achieved up to 5 days [ 232 ]. As demonstrated in another study, the nanoparticles effectively lowered intraocular pressure compared to the native drug due to the increased adhesion of NPs to the corneal surface for up to 4 h in vitro and up to 1 h in vivo (in pig eyes and rats) [ 233 ].…”
Section: Exploring Dna Nanostructures As Innovative Vehicles For Opht...mentioning
confidence: 99%